Positive Selection in the Light Zone of Germinal Centers - Nakagawa, Rinako; Calado, Dinis Pedro (Frontiers in Immunology, 2021)
Germinal centers (GCs) are essential sites for the production of high-affinity antibody secreting plasma cells (PCs) and memory-B cells (MBCs), which form the framework of vaccination. Affinity maturation and permissive selection in GCs are key for the production of PCs and MBCs, respectively. For these purposes, GCs positively select “fit” cells in the light zone of the GC and instructs them for one of three known B cell fates: PCs, MBCs and persistent GC-B cells as dark zone entrants. In this review, we provide an overview of the positive selection process and discuss its mechanisms and how B cell fates are instructed.